Framework to assess competitive positioning in manufacturing industries. (2017) - Kharub, Manjeet; Sharma, Rajiv Kumar
The purpose of this paper is to assess the competitive positioning of manufacturing industries, particularly micro, small and medium enterprises (MSMEs) using Porter Diamond Framework. In this study, the authors used both descriptive and empirical approach. In the descriptive analysis, the current status of each item has been analysed. In empirical analysis, six hypotheses were formulated and tested. From the results, it is observed that 10 out of 47 valid items show low PPS score (25% to 45%), 32 items show medium (46% to 75%) and only five items show high score, e.g., (PPS > 75%). Although all determinants were found significantly positive co-related with firm's competitiveness; demand condition was viewed as most important one with maximum value of Pearson coefficient (r = 0.663, p = 0.01). Factor condition was found as the least important among all determinants of Porter model as evident from r = 0.530, p = 0.01.